Nuove soggettività politiche del secondo Novecento: un percorso tra Jean-Paul Sartre, Frantz Fanon e Carla Lonzi - Fiorino, Vinzia (Itinerari, 2023)
In the immediate postwar period, Sartre was one of the most important and most influential philosophers because, by relating the themes of phenomenology with those of Marxism, he sought to enrich the reflection of the “philosophy of the subject.” This perspective, which envisaged a harsh confrontation with Hegel, profoundly marked the Italian cultural and philosophical debate in the long season of political movements, and accompanied the most significant changes that Italian society experienced during the 1970s. Carla Lonzi, who was the most important theorist of Italian Feminism, reflects on the foundation of an autonomous feminine subjectivity. The article brings Lonzi into conversation with Frantz Fanon and Jean-Paul Sartre, and leads her to consider the following question: Within which theoretical path was it possible to think of “unforeseen subjectivities” such as women and blacks? There is a morphological relationship between Frantz Fanon and Carla Lonzi, but also some significant differences which highlight the intersectionality between the categories of gender and race.